Redemption from plight: a qualitative study on reasons behind treatment decisions among Iranian male opioid users - Mostafa Amini-Rarani; Esmaeil Khedmati Morasae; Tahereh Pashaei; Maryam Moeeni (BMC, 2020)
Abstract Background Opioid use remains a significant cause of harm to individual health. Perceived motives are of the main factors that help lead a patient into seeking treatment voluntarily to obviate that harm. The current study expands on the literature by exploring when and how male users of opioids become motivated to voluntarily seek treatment services. Methods In a qualitative study in Isfahan city from January 2018 to March 2019, 55 male participants who had already started a variety of treatment services to withdraw their dependence on opioids were recruited. Selection of participants was based on a maximum variation purposive sampling strategy. Each participant took part in a unstructured interview to identify his motives for seeking opioid use treatment. Interviews were undertaken in eight different treatment centers. An inductive thematic analysis method was used to analyze the interviews. Results The findings highlight that Iranian male opioid users have different motivations to seek treatment. To be precise, the findings illuminate three global themes and six themes as treatment-seeking motives among the participants including; motives related to family (reason for family and reason of family), quality of life (adverse effects on personal lifestyle and health) and economic motives (financial failure and job failure). Conclusions The findings can improve our understanding of the motives for seeking treatment from the perspective of opioid patients who entered themselves into treatment. Particularly, these findings could help policymakers and treatment providers to better understand opioid-use patient's perceived concerns and fears as motives for treatment-seeking.